2015
DOI: 10.1002/cphc.201500075
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Energy and Spatial Distribution of Intragap Trap States in the TiO2 Photoanode of Dye‐Sensitized Solar Cells

Abstract: The energy and spatial distribution of intragap trap states of the TiO2 photoanode of dye-sensitized solar cells and their impact on charge recombination were investigated by means of time-resolved charge extraction (TRCE) and transient photovoltage (TPV). The photoanodes were built from TiO2 nanospheroids with different aspect ratios, and the TRCE results allowed differentiation of two different types of trap states, that is, deep and shallow ones at the surface and in the bulk of the TiO2 particles, respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
76
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 29 publications
(79 citation statements)
references
References 74 publications
3
76
0
Order By: Relevance
“…As ar esult, charger ecombination directly occurs among the free electrons and acceptors, exhibiting an almost constant recombination rate. [35] The reasonisascribed to the alternative recombination pathway at low voltage (i.e., the isoenergetic electrons transfer from surfacestate of the TiO 2 to the electrolyte acceptors), which cannot be described by multiple-trapping mechanism. Figure 1s hows the ideal multiple-trapping assistedc harge recombination;h owever,m odificationsa re often required when describing real experiments.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As ar esult, charger ecombination directly occurs among the free electrons and acceptors, exhibiting an almost constant recombination rate. [35] The reasonisascribed to the alternative recombination pathway at low voltage (i.e., the isoenergetic electrons transfer from surfacestate of the TiO 2 to the electrolyte acceptors), which cannot be described by multiple-trapping mechanism. Figure 1s hows the ideal multiple-trapping assistedc harge recombination;h owever,m odificationsa re often required when describing real experiments.…”
Section: Resultsmentioning
confidence: 99%
“…The simulation parameters are as follows: N c = 10 20 cm À3 , N T = 10 19 cm À3 ,[33][34][35] k B T = 25.8 meV, E c = E redox + 900 meV,and k c = 100 s À1 . The simulation parameters are as follows: N c = 10 20 cm À3 , N T = 10 19 cm À3 ,[33][34][35] k B T = 25.8 meV, E c = E redox + 900 meV,and k c = 100 s À1 .…”
mentioning
confidence: 99%
“…Therefore, the electron and hole transfers from perovskite to PbI 2 are forbidden; in other words, PbI 2 could not act as a trap state to capture charge carriers. In addition, the trap states are expected to localize at the surface or interface of perovskite particles, so films assembled from small particles may possess higher DOS due to the larger surface area . However, with the decrease in particle size, the contact between particles becomes more intimate and the neck area becomes larger (see Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…[54,55] In recent years, we have reported that time-resolved charge extraction (TRCE) could act as another effective candidate to study quantitatively the DOS distribution in dye-sensitized solar cells, quantum-dot-sensitized solar cells, and perovskite solar cells. [56][57][58][59][60] However,asignificant limitation of these methods is that the tested system should be connected to as hort or open circuit,s ot hey are unable to investigate the trap states in intrinsic perovskite films without selected electrodes. In contrast, transient infrareda bsorption spectroscopy can be used to measure the DOS distribution of thin films, but it is not easy to identify the characteristic optical signals and the requirement of instrumentsa nd technology is relatively high.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17] Nevertheless, the relatively high density of electronic trap states below the CB are a signifi cant drawback for the application of TiO 2 electrodes in solar cells. [19][20][21] One method to reduce the trap states in TiO 2 is doping. [19][20][21] One method to reduce the trap states in TiO 2 is doping.…”
mentioning
confidence: 99%